Analysis of Students Scientific Reasoning Ability and the Correlation to Students Cognitive Ability in Physics Learning - Kamaluddin Kamaluddin; Nurul Kami Sani; I Wayan Darmadi; Nurgan Nurgan (Postgraduate, University of Mataram, 2023)
This study aims to identify students scientific reasoning ability in Palu city and the correlation between students’ scientific reasoning abilities and their cognitive aptitude within the context of physics education. In this study, we adopted a descriptive quantitative research method where the respondents consist of four high schools in Palu city, namely SMAN 1, SMAN 7, SMAN 6, and SMAN 4 Palu. An instrument by Lawson (LCSTR) was adapted for this study and it consist of 12 items two tier multiple-choice that contains conservation of mass and volume, proportional thinking, control of variables, probabilistic thinking, correlational thinking, and hypothetical deductive reasoning. Meanwhile, for the cognitive understanding test, we utilized a static fluid concept comprehension test. The findings of this research using SPSS to analyzed find that Pearson correlation coefficient is 0,54 that revealed significant correlations between students’ scientific reasoning abilities and their cognitive aptitude in the context of physics learning. These correlations provided valuable insights into how these components influence each other and impact students’ performance and achievement in physics. The study’s result has implications for educators as a reference in the selection of models and methods of physics learning appropriate to train and develop students scientific reasoning skills.